Visual documentation of History: images in documentaries on the Civil War in the 21st century between 2000 and 2014 - Gómez Segarra, Manuel; Cabeza San Deogracias, José (Revista General de Información y Documentación, 2024)
The purpose of this research is to delve into how historical documentary audiovisual narration is constructed. It is based on the premise that images, as opposed to the predominance of text, are the fundamental and defining element of documentary language. In order to corroborate this idea, a detailed breakdown of the images used in the footage of documentaries on the Civil War made in Spain between 2000 and 2014 has been carried out. A classification has been made of the different types that exist and an analysis has been made of the uses given to them both, from a narrative perspective, as well as from the perspective of their contribution to supporting the topic in question. Finally, the use of material from fictional films and the elaboration of reconstructions have been examined in depth, as images that question the verisimilitude of the format. The article concludes that ’documentaries tell the story by creating a narration supported by images, thanks to their double and simultaneous documentary and narrative role.